Does growth attract FDI? - Sasi Iamsiraroj; Hristos Doucouliagos (Economics: The Open-Access, Open-Assessment E-Journal, 2015)
FDI is seen widely as a vital source of investment, technology transfer, and growth. The factors that attract FDI have been a longstanding source of debate. The authors present a comprehensive assessment of the accumulated evidence on one factor, the success of economic growth in attracting FDI. Meta-regression analysis is applied to 946 estimates from 140 empirical studies. The results confirm that, on average, economic growth is an important determinant of FDI. Overall, there is a positive correlation between growth and FDI and this is much larger among single country case studies than with cross-country analysis.
Keywords: O24; F21; 330; economic growth; FDI; meta-regression analysis